Real Time Monitoring for Drowsiness and Emergency Detection on Riders Using XD-58C Sensor - Qory Hidayati; Ridho Fadhillah (Journal of Telematics and Informatics, 2020)
Drowsiness that felt by the driver will affect the security of someone when driving. It can be seen that many accidents cause death due to drowsiness when driving. Due to the effects of fatigue after some busy activities and the responsibility to keep going home. However, this is not supported by the motorist's awareness of not continuing the journey and resting for a while until the physical condition returns to normal. So to reduce the number of accidents that occurred needed a capable tool of detecting sleepiness through the state's heartbeat using a heartbeat sensor (XD-58C) to the rider who can awaken directly by using vibration motors and buzzer, and if an emergency occurs, namely when the driver crashed, the tool will send point location via SMS to the families, hospitals and police stations using GSM module SIM800L, point locations that are read by an integrated GPS module with microcontroller arduino during an accident that can be used by the driver. Keywords: XD-58C Sensor, Drowsiness Detection System, Emergency Detection, GSM SIM800L, modul GPS